Band-like transport in high mobility unencapsulated single-layer MoS2 transistors - Jariwala, Deep; Sangwan, Vinod K.; Late, Dattatray J.; Johns, James E.; Dravid, Vinayak P.; Marks, Tobin J.; Lauhon, Lincoln J.; Hersam, Mark C. (Applied Physics Letters, 2013)
Ultra-thin MoS2 has recently emerged as a promising two-dimensional semiconductor for electronic and optoelectronic applications. Here, we report high mobility (>60 cm(2)/Vs at room temperature) field-effect transistors that employ unencapsulated single-layer MoS2 on oxidized Si wafers with a low level of extrinsic contamination. While charge transport in the sub-threshold regime is consistent with a variable range hopping model, monotonically decreasing field-effect mobility with increasing temperature suggests band-like transport in the linear regime. At temperatures below 100 K, temperature-independent mobility is limited by Coulomb scattering, whereas, at temperatures above 100 K, phonon-limited mobility decreases as a power law with increasing temperature. (C) 2013 AIP Publishing LLC.